LOGARITMOS DE NÚMEROS NEGATIVOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
The great importance in the history of mathematics, concerning the study of logarithms, is consensual, both because the purpose for which they were created and because of their various applications. When this content is taught in high school, its definition and its basic properties to the positive real numbers are presented, but logarithms for negative numbers are not addressed. This work has as main objective the depth study of obtaining the logarithms for negative numbers: historical context, properties, exceptions and particularities, complex numbers and a study of the Euler equation. With the derived results of this study it is expected to provide input to obtain a methodology for teaching this subject, even superficially, in high school.
Keywords: logaritmos; números complexos; equação de Euler; logarithms; complex numbers; Euler equation; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA